Global Financing Facility investments for vulnerable populations: content analysis regarding maternal and newborn health and stillbirths in 11 African countries, 2015 to 2019 - Mary Kinney; Meghan Bruce Kumar; Issa Kaboré; Joël Kiendrébéogo; Peter Waiswa; Joy E. Lawn (Global Health Action)
Background The Global Financing Facility (GFF) was launched in 2015 to catalyse increased domestic and external financing for reproductive, maternal, newborn, child, adolescent health, and nutrition. Half of the deaths along this continuum are neonatal deaths, stillbirths or maternal deaths; yet these topics receive the least aid financing across the continuum. Objectives To conduct a policy content analysis of maternal and newborn health (MNH), including stillbirths, in GFF country planning documents, and assess the mortality burden related to the investment. Methods Content analysis was conducted on 24 GFF policy documents, investment cases and project appraisal documents (PADs), from 11 African countries. We used a systematic data extraction approach and applied a framework for analysis considering mindset, measures, and money for MNH interventions and mentions of mortality outcomes. We compared PAD investments to MNH-related deaths by country. Results For these 11 countries, USD$1,894 million of new funds were allocated through the PADs, including USD$303 million (16%) from GFF. All documents had strong content on MNH, with particular focus on pregnancy and childbirth interventions. The investment cases commonly included comprehensive results frameworks, and PADs generally had less technical content and fewer indicators. Mortality outcomes were mentioned, especially for maternal. Stillbirths were rarely included as targets. Countries had differing approaches to funding descriptions. PAD allocations are commensurate with the burden. Conclusions The GFF country plans present a promising start in addressing MNH. Emphasising links between investments and burden, explicitly including stillbirth, and highlighting high-impact packages, as appropriate, could potentially increase impact.